PERANCANGAN MOLD SET KOMPONEN HANDLE PINTU MOBIL DENGAN MATERIAL ALUMUNIUM 6061 - Jatira; Apang Djafar Shieddieque; Wilman Adi Nugraha Wilman (Sekolah Tinggi Teknologi Wastukancana, 2023)
In the world of the manufacturing industry, developments and needs are increasing every day and very rapidly. Many parts and components in automotive production are very important and very much too because each component has its own function and use. There are many alternatives and development of materials for component manufacturing in the automotive world which aim to cut production costs and efficiency. To overcome this condition, the authors tried to research and make a Mold for the Avansa car door handle using HIPP (High Impact PolyPropilane) material. Generally, not many HIPP use it in the automotive industry. Making this door hendle using the Hot Compression process. Among other things, hot compress is the process of making a product by using heat and pressure to form the desired product. So far, making molding is less precise because mold making is not in accordance with the manufacturing process, therefore the author uses a CNC (Computer numarical control) machine for this molding-making process, the molding process using this CNC machine aims to make the results more precise and more accurate. more as desired.